Group 13 element containing conformationally rigid "N–E–N" heteroatomic bridged [3.3](2, 6)pyridinophanes (E = B, Al). Issue 64 (24th July 2018) - Bawari, Deependra; Negi, Chandrakala; Jaiswal, Kuldeep; Prashanth, Billa; Choudhury, Angshuman Roy; Singh, Sanjay
Abstract : Donor–acceptor interactions (Npy⋯E) have been utilized to assemble conformationally rigid [3.3](2, 6)pyridinophanes containing group 13 elements. Abstract : The first examples of group 13 element containing pyridinophanes have been assembled using heteroatom N–E–N bridges (E = B, Al). The presence of B and Al as acceptor atoms in the bridges and their coordination with pyridine nitrogen has a very strong influence on the conformational rigidity of the pyridinophanes.